KOMUNIKASI INFORMASI EDUKASI MASTITIS PADA PETERNAK USAHA RAKYAT DI KUD SUMBER MAKMUR NGANTANG KABUPATEN MALANG JAWA TIMUR - Indah Amalia Amri; D. Qosimah; N. Rickyawan; A.A. Nurmaningdyah (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2020)
One of the main problems of dairy farmers is mastitis, this disease is often dairy cows during lactation, causing a decrease in milk production to 80%, milk quality down, and milk cannot be consumed or marketed during the treatment period. In this community service, the target partners are dairy farmers in KUD Ngantang who have 1-9 cows, traditional breeders generally have limited facilities and infrastructure and do not understand the proper management of maintenance of dairy cows, which can lead to ongoing disease events over and over. The purpose of this community service is the transfer of knowledge to dairy farmers about mastitis, and conducting social services in the form of mastitis examination. Community service methods include 1. Counseling and discussion, 2. Evaluation in the form of questionnaire distribution. The results obtained after the evaluation by giving questionnaires are known that, the total number of livestock owned by community service participants Sumber Makmur KUD is 386 dairy cows (130 calves, 85 pregnant cow, 171 lactation cow) and ownership status belongs to the farmers themselves, all breeders already know about mastitis and most have gotten and experienced mastitis cases in treated cows. The handling of mastitis cases has mostly involved animal health workers. In the milking procedure, most of the antiseptic precautions taken after the milking process have been taken. Farmer responses based on the questionnaire results are known that community service activities are very useful and can be applied. The speakers also get a positive response in delivering material and answering questions from farmers.